First results on modeling of ITER infrared images. (21st January 2016) - Kočan, M; Reichle, R; Aumeunier, M-H; Gunn, J P; Kajita, S; Le Guern, F; Lisgo, S W; Loarer, T; Kukushkin, A S; Sashala Naik, A; Rigollet, F; Stratton, B
Abstract: Infrared (IR) images of the ITER wide angle viewing system are modeled for the baseline plasma equilibrium and partially detached tungsten divertor, taking into account the three-dimensional structure of the first wall and the divertor. The modeling includes a comprehensive chain of calculations from the heat load specifications up to the synthetic, reflection-free IR images of the surface temperature, T surf . The effect of the optical blur due to finite IR detector size and diffraction/aberrations—approximated by a Gaussian filter—on the measured T surf is investigated. The optical blur characterized by σ  = 0.7 pixel (approximately twice the diffraction limit) leads to underestimation of T surf, max on the inner vertical divertor target and near the upper X-point by <6% and <4%, respectively. This is within the required measurement accuracy of 10%. Larger underestimation of T surf, max (<12%) is observed on the outer vertical divertor target. The study demonstrates the importance of keeping the performance of the optical system as close as possible to the diffraction limit.